2016
DOI: 10.1080/13814788.2016.1232386
|View full text |Cite
|
Sign up to set email alerts
|

Comparing initial diagnostic excision biopsy of cutaneous malignant melanoma in primary versus secondary care: A study of Irish National data

Abstract: Initial excision biopsy carried out in general practice does not lead to a poorer outcome. ABSTRACT Background:The incidence of melanoma is rising worldwide. Current Irish guidelines from the National Cancer Control Programme state suspicious pigmented lesions should not be removed in primary care. There are conflicting guidelines and research advising who should remove possible melanomas. Objectives: To determine whether initial diagnostic excision biopsy of cutaneous malignant melanoma in primary versus seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Finally, using the published estimates, a pooled estimate of the relative hazard of death after having a melanoma excised in secondary care versus primary care (as the reference group) for the 9367 Scottish and the 7116 Irish patients [13] was calculated. In order to utilise the published risk estimates from Doherty et al [13], we had to swap our reference group to be primary care in this pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, using the published estimates, a pooled estimate of the relative hazard of death after having a melanoma excised in secondary care versus primary care (as the reference group) for the 9367 Scottish and the 7116 Irish patients [13] was calculated. In order to utilise the published risk estimates from Doherty et al [13], we had to swap our reference group to be primary care in this pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This study reported that 8.5% of melanomas in Ireland were removed in primary care with a non-inferior outcome, but adjusted for a limited number of potential confounders. [13] Using linked national data, we investigated whether patients diagnosed with cutaneous melanoma in Scotland between 2005 and 2013 had different mortality and morbidity outcomes depending on whether excision was performed in primary or secondary care. We controlled for a greater number of confounders and also produced the first international pooled estimate of relative mortality for those having a melanoma initially excised in primary versus secondary care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It resects the lesion beyond its margins to an extent of 1-3 mm according to NCCN (National Comprehensive Cancer Network) guidelines or 1-2 mm according to AJCC guidelines. This limit is crucial, given that avoiding lymphatic destruction ensures feasible detection of sentinel lymph nodes[ 6 - 8 ]. The other types of biopsy can potentially lead to misdiagnosis and inaccurate staging.…”
Section: To the Editormentioning
confidence: 99%
“…Several studies from the United Kingdom (UK) have reported poorer quality of surgery for skin cancers in general practice compared to hospital settings [6][7][8][9], although one study showed that GPs compared favourably to skin specialists and outperformed hospital non-specialists in the excision of squamous cell carcinomas [10]. In studies from both the UK [11] and Ireland [12], the outcomes for primary excision of malignant melanoma were shown to be equivalent between GP and hospital providers. A community-based surgery audit from the UK, which examined 6138 procedures, concluded that GP minor surgery was safe and prompt and that GPs working within a managed framework performed better than less well-supported GPs [13].…”
Section: Introductionmentioning
confidence: 99%